2022
DOI: 10.1016/j.jamda.2021.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Previous SARS-CoV-2 Infection, Age, and Frailty Are Associated With 6-Month Vaccine-Induced Anti-Spike Antibody Titer in Nursing Home Residents

Abstract: Objectives Older nursing home residents make up the population at greatest risk of morbidity and mortality from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. No studies have examined the determinants of long-term antibody responses post vaccination in this group. Design Longitudinal cohort study. Setting and Participants Residents from 5 nursing homes assessed before vaccination, and 5 weeks and 6 months post vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…A pool of serum from 27 PCRpositive healthcare workers from IMM was used for assay calibration. In a study of vaccine-induced immune responses, 86 residents of nursing homes in Dublin, Ireland, were followed before and after receiving two doses of the Pfizer BNT162b2 vaccine [21]. Samples were collected at baseline and 5 weeks and 6 months after the second dose.…”
Section: Samplesmentioning
confidence: 99%
“…A pool of serum from 27 PCRpositive healthcare workers from IMM was used for assay calibration. In a study of vaccine-induced immune responses, 86 residents of nursing homes in Dublin, Ireland, were followed before and after receiving two doses of the Pfizer BNT162b2 vaccine [21]. Samples were collected at baseline and 5 weeks and 6 months after the second dose.…”
Section: Samplesmentioning
confidence: 99%
“…Therefore, we concluded that the only variable that showed an association with having more severe adverse reactions was the existence of a previous positive serology. Having had a previous COVID-19 infection was the strongest predictor of anti-spike antibody titers at 3 and 6 months [ 21 ] and this would justify the higher frequency of severe reactions observed in our sample, compared with the results obtained in other studies [ 22 ].…”
Section: Discussionmentioning
confidence: 65%
“…It has to be mentioned that our nursing home under study was in the upper range of SARS-CoV-2 infection during the first pandemic wave [ 23 , 24 ]. In older nursing home residents, SARS-CoV-2 infection history was the strongest predictor of anti-spike antibody titers at 6 months, whereas age and frailty were independently associated with lower titers at 6 months [ 21 ]. The persistence of IgG after vaccination in nursing home residents is high (95.2%) and was similar to the rate found in our study [ 16 ], regardless of the degree of frailty [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reliable measures of frailty including the CFS and have been described in a limited number of COVID-19 vaccine studies in the nursing home setting. 25 , 26 , 57 A single-site nursing home study in France had little variability in frailty status, which limited their ability to detect the association of frailty with antibody and cellular responses. 25 Interestingly, a study from Poland with mixed frailty status of participants described little effect of frailty on antibody responses to the Pfizer mRNA vaccine, though their measurements did not include assessment past 2-weeks post second vaccine dose.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 21 , 52 , 53 Higher quantity antibody titers detected with ELISA are associated with protection from adverse health-related outcomes from COVID-19 and influenza, 54 56 but frailty and older age have been associated with waning of COVID-19 vaccine-elicited antibody. 7 , 13 , 19 , 25 , 57 However, quantitative antibody assays are incomplete descriptors of immunity to SARS-CoV-2. 58 A surrogate of protection from infection is antibody neutralization, which commonly targets the SARS-CoV-2 spike protein receptor binding domain (RBD).…”
Section: Introductionmentioning
confidence: 99%